KARAKTERISTIK DAN GAYA KEPEMIMPINAN ORGANISASI SEKTOR PUBLIK - Priyastiwi Priyastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
This paper explains the differences in the characteristics of the leadership of the public sector with the private sector. Public sector leadership which emerged as a distinctive leadership and autonomous domain, although the debate continues as compared to business leadership research. This article opens the way for a promising new research on arising of process leadership from the collaboration between business organizations and governance. Leadership training has failed to take into account the operational and the public sector organizational context. This article shows that in the future, the role of ethics and integrity of a leader as well as the importance of emotion and spirituality. A leader who has the ability to see others as people with a variety of emotions, beliefs, skills, knowledge and abilities, and to drive the whole organization towards a clear vision. The impact of different leadership styles are more dependent on contextual factors such as social and cultural environment in which public sector organizations operate.